Patent Litigation as an Information-Transmission Mechanism - Choi, Jay Pil (American Economic Review, 1998)
Patent litigation reveals important information about the validity of the contested patent to other potential entrants. This paper explores the implications of such informational externalities for entry dynamics in the presence of multiple potential entrants. The nature of the entry game can be one of either waiting or pre-emption depending on the degree of patent protection. Therefore, the payoffs for the patentee and the initial imitator are discontinuous in the degree of patent protection. Furthermore, strengthening intellectual property rights is not necessarily desirable for the patentee. The analysis may also help explain the apparently puzzling practice of delaying patent suits.